Literasi Hukum Digital: Mitigasi Risiko Pencemaran Nama Baik bagi Pelajar Sekolah Menengah Atas: Digital Legal Literacy: Mitigating Defamation Risks for High School Students - Handoyo Prasetyo; Bambang Waluyo; Subakdi Subakdi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Low digital legal literacy among high school students has led to high vulnerability to defamation charges. This community service initiative aims to mitigate such risks through a legal literacy dissemination method, specifically by producing scientific articles as a medium for independent public education. The primary focus of this study is to translate complex norms in the Electronic Information and Transactions (ITE) Law and the new Criminal Code (KUHP) into practical mitigation guidelines for students. The results indicate that providing a knowledge infrastructure through scientific writing offers an authoritative reference for both students and guidance counselors in distinguishing between freedom of expression and criminal defamation. In conclusion, this asynchronous dissemination strategy effectively provides a sustainable preventive solution, unrestricted by space or time. This article serves as a practical guide to building students' digital legal resilience and protecting future digital footprints.